EFEKTIVITAS MODEL TEAMS GAMES TOURNAMENT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Azka Hanifa, Mila; Adi Budiman, Indra (Papanda Publisher, 2023)
Abstract should be written briefly and clearly. Abstract must contain 150-250 words. The contents of the Abstract are written in one paragraph without including quotes, pictures, or tables. The abstract contains a brief description of the problem, solution, research objectives, methods used, instruments, research subjects (who, where, how many), research resu lts, and conclusions. The emphasis on writing abstracts is mainly on research results and conclusions. Keywords need to be included to describe the area of the problem being studied and the main terms that underlie the implementation of the research. In this elementary school students are required to master all fields of study, how to solve problems. Mathematics is a subject that has an important role in everyday life. The method in this journal is a qualitative method and literature study. The results of the findings are related to the understanding of the TGT method, as well as the steps that must be taken and the flexibility contained in this method in learning in elementary schools.